Controle de qualidade aplicado a inspeção visual de pavimentos flexíveis urbanos - Silva, Leandro Marzari (2017)
The evaluation of the pavement condition is an engineering technique widely used in systems of pavement management and, its aim is to offer a diagnostic about the quality of them from the indexes calculated – among other ways through the manual evaluation of the defects. These data of pavement conditions are used by managers to take their decisions related to the conservation and maintenance of road helping in the definition of the kinds of treatment, priorities and the allocation of resources to improve these actives. Therefore, a technique used is the visual inspection of the defects by trained evaluators that go through the roads registering the defects. Nevertheless, such evaluation depends on the individual judgement of each technician. Thus, some variability of the data are expected in the data obtained by different technicians – what depends on the greatness of the variability, it could represent contradiction in the data and create wrong decisions as well as impact negatively the management system. For this reason, it is importantto check the quality of such information before and during de evaluation. This is the reasonthis paper presents an application of the control of quality to the data collection of urban flexible pavement through visual inspections in order to check the data collected by different evaluators. The procedure was tested through the evaluation of some sections of urban ways in the city of Xanxerê in the state of Santa Catarina and its main intention was to check the quality of the data collected by four technicians, through verification of the variability of the data and the diversion related to the values of reference. The accuracy of the data was analyzed through the coefficient of the variation and the exactness through the diversion comparing to the data of control. After analyzing the data we realized that the procedure is valid because it could show the variability and the bias of the data leading to the improvement of the technicians and obtaining more consistent data, proving the efficiency of the control of quality in the visual inspections of urban flexible pavements.